Barriers and Facilitators to Implementation of Antibiotic Stewardship Programmes in Hospitals in Developed Countries: Insights From Transnational Studies - Rzewuska, Magdalena; Duncan, Eilidh M.; Francis, Jill J.; Morris, Andrew M.; Suh, Kathryn N.; Davey, Peter G.; Grimshaw, Jeremy M.; Ramsay, Craig R. (Frontiers in Sociology, 2020)
Objectives: To identify any perceived influences on implementation of antibiotic stewardship programmes (ASPs) in hospitals, across healthcare systems, and to exemplify the use of a behavioural framework to conceptualise those influences. Methods: EMBASE and MEDLINE databases were searched from 01/2001 to 07/2017 and reference lists were screened for multi-country studies that reported barriers and/or facilitators to implementing actual or hypothetical ASPs or ASP-supporting strategies. Extracted data were synthesised using content analysis with the Theoretical Domains Framework as an organising framework. Commonly reported influences were quantified. Results: From 3196 abstracts 75 full-text articles were screened for inclusion. Eight studies met the eligibility criteria. The number of countries involved in each study ranged from 2 to 36 (total participants 1849). North America, Europe and Australasia had the strongest representation. Participants were members of special interest groups, designated hospital representatives or clinical experts. Ten of the 14 theoretical domains in the framework were present in the results reported in the included studies. The most commonly reported (≥4 out of 8 studies) influences on ASP implementation were coded in the domain ‘environmental context and resources’ (e.g., problems with data and information systems; lack of key personnel; inadequate financial resources) and ‘goals’ (other higher priorities). Conclusions: Despite a substantial transnational research effort, there is evidence from international studies of substantial barriers to implementing ASPs in hospitals. Large-scale efforts to implement hospital antibiotic stewardship globally will be needed to overcome the identified barriers. We have provided an example of taking a behavioural approach to identify potential influences. Systematic review registration: PROSPERO registration number CRD42017076425.